(3aJGhi ddEeGe jMji Hf MeRI Hf Ydi GdYdhis - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hef LgI CejQ GdeDefjf Ydjg GdSdGe hSGFQ GdCFeI hChdGOg s
(3BNQgG (B:s
(3hLYdfG dce hdGjI GdJUQa hab GdTQY hefhGdg hbGYOJg hefgGLg hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B19s
(3eLehYI efgGs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3eLGejY (B10) s
Keywords: (3abg GdePGgH GdCNQis